Malaysian sign language database for research - Maarif, Haris Al Qodri; Akmeliawati, Rini; Bilal, Sara (2012)
Malaysian Sign Language (MSL) is the main language that is commonly used by the hearing and speech impaired person in Malaysian. The SL (SL) involves hand movement, and hand gestures. In order to help people who are not familiar, but need to understand a particular SL, an automatic SL recognition system is highly required. The research in this area, especially for MSL, has been conducted by many researchers, but one of the main challenges in this research is the availability of suitable sign database for the recognition. The existing databases, especially which of MSL database, are provided often without a proper standard of image resolution, structure and compression that are sufficiently good for research purpose. To provide comprehensive information for the research on MSL, the MSL database is highly required. In this project, a MSL database is developed. The database is the first of the kind and developed for research purpose. In general, the structure of the MSL database is classified into groups that deal with the hand movement, hand gestures, and hand location. For the classification in our proposed database, the MSL is classified into One Hand, Two Hands, Static, and Dynamic. This classification is made to ease researchers in defining the research method for each type offhand signing.